A divergence theorem for non-compact Riemannian manifolds: a dynamical approach. (13th February 2019) - Melo, Ítalo; Pujals, Enrique
Abstract: In this paper we use a dynamical approach to prove some new divergence theorems on complete non-compact Riemannian manifolds.